Approaches to inform redevelopment of brownfield sites: An example from the Leeds area of the West Yorkshire coalfield, UK. (September 2015) - Burke, H.; Hough, E.; Morgan, D.J.R.; Hughes, L.; Lawrence, D.J.
Highlights: Geological information can better characterise the near-surface in coalfield areas. This information can be used to identify problematic ground conditions. Artificial ground associated with coal mining or landfill can be quantified. A holistic approach from investment through to ultimate redevelopment is recommended. Abstract: Government-led regeneration schemes and policies encouraging the use of brownfield land present a challenge, particularly in coalfield areas. Coalfields have typically experienced multiple phases of development and can be susceptible to a suite of problematic ground conditions that may be rooted in the near-surface geology or result from anthropogenic activity. Such problems, related to the nature of void backfill, undermined and unstable ground and the presence of contaminated land in the near-surface, may deter investment in the very areas earmarked for redevelopment. An understanding of previous developments within coalfields is required to identify potential geological hazards, so that regeneration proposals include measures that address these issues. Public records of landfill and site investigations, and minerals exploration including opencast mine plans can reveal the distribution, thickness and high-level descriptions of fill materials, although the coverage of data typically precludes a comprehensive analysis of entire cities. The best way to show the spatial distribution of fill materials is currently as a two dimensional national/regional scale dataset. Depending on the distribution of data points, however, 3D modelling can be possible, which is much more detailed and accurate. Focusing on the heavily urbanised county of West Yorkshire in northern England, the assessment of opencast coal mining on the landscape and benefits of quantifying the impact are discussed. We demonstrate how certain types of publicly available data allow a greater understanding of the interaction between human activity and natural superficial and bedrock geology. If successful, this approach can help lessen the impact of delays and increased financial costs caused by unforeseen ground conditions.